2014
DOI: 10.1103/physrevlett.112.023903
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary Bending Plasmonic Light Waves

Abstract: We demonstrate the generation of self-accelerating surface plasmon beams along arbitrary caustic curvatures. These plasmonic beams are excited by free-space beams through a two-dimensional binary plasmonic phase mask, which provides the missing momentum between the two beams in the direction of propagation, and sets the required phase for the plasmonic beam in the transverse direction. We examine the cases of paraxial and nonparaxial curvatures and show that this highly versatile scheme can be designed to prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 21 publications
1
92
1
Order By: Relevance
“…Moreover, an experimental analysis is carried out in order to support the theoretical predictions. The findings of this work can be extended to other reported caustic beams with arbitrary complex trajectories [18][19][20] and other types of selfbending and self-healing beams such as Mathieu and Weber beams [21].…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, an experimental analysis is carried out in order to support the theoretical predictions. The findings of this work can be extended to other reported caustic beams with arbitrary complex trajectories [18][19][20] and other types of selfbending and self-healing beams such as Mathieu and Weber beams [21].…”
Section: Introductionmentioning
confidence: 79%
“…Since the wave-vector of SPPs is larger than that of free space beams, a special grating should be constructed on the surface in order to excite these beams from free-space and set their required transverse profile. Quite recently we have extended this concept of arbitrary "bending" to the field of SPP waves [6], thereby generating accelerating beams with different polynomial and exponential trajectories. Furthermore, the non-paraxial Mathieu and Weber SPP beams were also realized [7].…”
Section:  mentioning
confidence: 99%
“…Li et al [18], [19] experimentally realized a plasmonic Airy beam by directly coupling a laser beam, the plane wave incidence and the point source with a carefully designed, nonperiodically arranged sliver nanocave array also fabricated by FIB milling. Epstein and Arie [20] excited self-accelerating plasmonic beams along several different polynomial and exponential trajectories by free-space beams through two-dimensional binary plasmonic silver phase masks fabricated by EBL. Arie et al [21] demonstrated and experimentally converted the free space laser beam to Mathieu and Weber SPP beams by the silver plasmonic holograms written also by using EBL.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, there are mainly two kinds of methods to form plasmonic curved waves at metallic surface: 1) directly coupling free-space curved beams to surface plasmon polariton (SPP) through a metallic coupler [4] and 2) coupling laser beams to curved SPP with engineered nanoscale specific metallic phase masks [17]- [20]. For the first kind of method, Zhang et al [4] coupled 1-D free-space Airy beams to plasmonic Airy beams through a gold grating fabricated by electron beam lithography (EBL).…”
Section: Introductionmentioning
confidence: 99%